PENINGKATAN MOTIVASI BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SD LAB SCHOOL UNNES MELALUI ROLE PLAYING - Faimaya; Puji Rahayu; Nasya Oktavia Romadhoni; Bilqis Azmi A.P; Rina Nuraeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the improvement of students’ learning motivation in Pancasila Education through the implementation of the role-playing method in fourth-grade students at SD Lab School UNNES. The problem addressed in this research is the low learning motivation of students, as indicated by the initial pretest average score of 78.5%, which did not meet the classical mastery standard. This study employed a quantitative approach using a One Group Pretest–Posttest Design. The sample consisted of 12 students selected through purposive sampling. Data were collected through pretest, posttest, and documentation, and were analyzed using descriptive quantitative techniques by calculating the mean scores and comparing the results before and after treatment. The findings show a significant increase in students’ learning motivation after the application of the role-playing method. The posttest average score increased to 87.5%, surpassing the classical mastery criteria of 85%. In addition, all students achieved individual mastery, with a notable shift in the distribution of learning motivation categories from lower to higher levels. These results indicate that role-playing is an effective learning strategy to enhance students’ learning motivation and understanding of Pancasila values through active participation and experiential learning. This study contributes to strengthening learning practices that emphasize student engagement and character development in elementary schools. Penelitian ini bertujuan untuk menganalisis peningkatan motivasi belajar Pendidikan Pancasila melalui penerapan metode role playing pada siswa kelas IV SD Lab School UNNES. Masalah yang dikaji dalam penelitian ini adalah rendahnya motivasi belajar siswa, yang terlihat dari nilai rata-rata pretest sebesar 78,5% dan belum memenuhi standar ketuntasan klasikal.This study employed a quantitative approach using a quasi-experimental design with a One Group Pretest–Posttest model. Sampel penelitian berjumlah 12 siswa yang dipilih melalui teknik purposive sampling. Pengumpulan data dilakukan melalui pretest, posttest, dan dokumentasi, kemudian dianalisis menggunakan teknik deskriptif kuantitatif dengan menghitung rata-rata nilai serta membandingkan hasil sebelum dan sesudah perlakuan. Hasil penelitian menunjukkan adanya peningkatan motivasi belajar yang signifikan setelah diterapkannya metode role playing. Nilai rata-rata posttest meningkat menjadi 87,5% dan telah melampaui standar ketuntasan klasikal sebesar 85%, serta seluruh siswa mencapai ketuntasan belajar. Selain itu, terjadi pergeseran kategori motivasi dari tingkat rendah ke tingkat lebih tinggi. Temuan ini menunjukkan bahwa metode role playing efektif dalam meningkatkan motivasi belajar dan pemahaman siswa terhadap nilai-nilai Pancasila melalui pengalaman belajar yang aktif dan bermakna, serta memberikan kontribusi terhadap penguatan praktik pembelajaran berorientasi karakter di sekolah dasar.